Effects of Surgical and Non-surgical Periodontal Therapy on Renal Function and Inflammatory Biomarkers and Mortality in Patients with Chronic Kidney Disease: An Umbrella Review - Anny Marcela Vivares-Builes; María Teresa Pertúz-Rondón; German Márquez-Toro; Carlos Pizarro-Herrera; Andrés Alonso Agudelo-Suarez; Carlos M. Ardila (Odovtos - International Journal of Dental Sciences, 2026)
Periodontitis and chronic kidney disease (CKD) share common pathophysiological mechanisms, with periodontitis acting as a chronic inflammatory comorbidity that exacerbates systemic inflammation in CKD patients. This study aimed to analyze the effect of surgical and non-surgical periodontal therapy on renal function, inflammatory biomarkers, and mortality in patients with CKD according to the available evidence. An umbrella review was conducted, including systematic reviews and meta-analyses from databases such as PubMed, Clinical Key, Scopus, Cochrane, Scielo, and Google Scholar. Methodological quality was assessed using AMSTAR-2, and reporting quality with PRISMA. Five systematic reviews and meta-analyses, encompassing 21 primary studies, were analyzed. The evidence indicates that periodontal therapy significantly reduces systemic inflammatory biomarkers like IL-6 and C-reactive protein, while also improving renal function markers, including an increased glomerular filtration rate. Non-surgical periodontal therapy was associated with a statistically significant reduction in mortality and cardiovascular-related morbidity, especially with intensive therapy and follow-up. These findings suggest that periodontal treatment may benefit renal health by reducing systemic inflammation and lowering mortality risks linked to cardiovascular complications. However, the heterogeneity of study designs and analyzed variables limits the ability to draw definitive conclusions. Future high-quality research is necessary to clarify these associations.